Clinical assessment of micronutrient deficiencies in 2-6 years old children: a survey with pediatricians - Gungam, Praveena; Kadhe, Ganesh; Shaikh, Irfan A. (International Journal of Contemporary Pediatrics, 2021)
Background: Worldwide, at least fifty percent of children, younger than 5 years of age, suffer from micronutrient, protein and calorie deficiencies causing negative impact on health. Our study aims to understand the pediatricians’ perspectives on diagnosis and management of these micronutrient deficiencies (MND). Methods: A cross sectional questionnaire-based survey of 490 pediatricians, wherein the questionnaire focused on prevalence, causes, diagnosis, management and long-term impact of micronutrient deficiencies in children aged 2 to 6 years. Results: Majority of pediatricians (94%) commonly see MNDs in their clinical practice; with 94% pediatricians seeing MNDs in stunted children, 93% in wasted and 89.0% in obese children. About 50–90% pediatricians reported calorie, protein, vitamins and mineral deficiencies. Not eating a balanced diet was the cause of nutrient deficiency as per 97% pediatricians, while about 93-97% opined MNDs also cause frequent illness, lack of energy/weakness, loss of weight or causes thinness. All pediatricians believe that minerals, vitamins and proteins are important for immunity and bone development. Also, 88% pediatricians believe multiple MNDs can be evaluated by physical examination and clinical history; and about 40% pediatricians suggest intervention to 25-50% children. Also, they believe that MNDs impact long-term health outcomes like growth, cognitive development, metabolic development and social development. Conclusions: Micronutrient deficiencies contribute to lack of energy, frequent illness, and compromised immune system which in turn have short-term and long-term impact on overall growth and development. Hence there is a need to assess and address the MNDs at the earliest.